Synthesis, Characterization and Biodistribution Studies of 125I-Radioiodinated di-PEGylated Bone Targeting Salmon Calcitonin Analogue in Healthy Rats - Yang, Y.; Bhandari, K.; Panahifar, A.; Doschak, Michael (AAPS, 2013)
Purpose: The objective of this study was to prepare a bisphosphonate (BP) mediated bone targeting di-PEGylated salmon calcitonin analogue sCT-2(PEG-BP) as a novel bone targeting pharmaceutical. Methods: HPLC was used for isolation of sCT-2(PEG-BP) from the reaction mixture, followed by determination of possible PEGylation sites by trypsin digestion. Stability of the compound over time, bone mineral affinity using hydroxyapatite, and biodistribution in normal rats after radiolabeling of sCT-2(PEG-BP) or control sCT with 125I was evaluated. Results: PEGylated sCT analogues were synthesized, and sCT-2(PEG-BP) was isolated by HPLC and confirmed by MALDI-TOF and ICP-MS. MALDI-TOF analysis of trypsinized fragments suggested Cys1 (or Lys11) and Lys18 to be the two PEGylation sites. Bone mineral affinity test showed sCT-2(PEG-BP) or 125I-sCT-2(PEG-BP) exhibited significantly increased bone mineral affinity over sCT or 125I-sCT, respectively. sCT-2(PEG-BP) remained stable for at least 1 month. In vivo biodistribution study showed significantly increased bone retention and prolonged plasma circulation time for sCT-2(PEG-BP) compared to the control sCT. Conclusion: Those results support sCT-2(PEG-BP) as a promising new drug candidate for the treatment of resorptive and/or maladaptive bone conditions, such as Osteoporosis, Osteoarthritis, Rheumatoid Arthritis, Paget’s disease and bone cancers.